Mindfulness (Boston, 2017)
The benefits of mindfulness include better performance, heightened creativity, deeper self-awareness, and increased charisma?not to mention greater peace of mind. This book gives you practical steps for building a sense of presence into your daily work routine. It also explains the science behind mindfulness and why it works and gives clear-eyed warnings about the pitfalls of the fad. This volume includes the work of: Daniel Goleman Ellen Langer Susan David Christina Congleton This collection of articles includes ?Mindfulness in the Age of Complexity,? an interview with Ellen Langer by Alison Beard; ?Mindfulness Can Literally Change Your Brain,? by Christina Congleton, Britta K. H?lzel, and Sara W. Lazar; ?How to Practice Mindfulness Throughout Your Work Day,? by Rasmus Hougaard and Jacqueline Carter; ?Resilience for the Rest of Us,? by Daniel Goleman; ?Emotional Agility: How Effective Leaders Manage Their Thoughts and Feelings,? by Susan David and Christina Congleton; ?Don?t Let Power Corrupt You,? by Dacher Keltner; ?Mindfulness for People Who Are Too Busy to Meditate,? by Maria Gonzalez; ?Is Something Lost When We Use Mindfulness as a Productivity Tool?? by Charlotte Lieberman; and ?There Are Risks to Mindfulness at Work,? by David Brendel. How to be human at work. The HBR Emotional Intelligence Series features smart, essential reading on the human side of professional life from the pages of Harvard Business Review. Each book in the series offers proven research showing how our emotions impact our work lives, practical advice for managing difficult people and situations, and inspiring essays on what it means to tend to our emotional well-being at work. Uplifting and practical, these books describe the social skills that are critical for ambitious professionals to master.
Keywords: Mindfulness (Psychology)